ترجيح اسباب النزول في جامع البيان عن تاويل اى القران للطبري في ضوء سورة الإخلاص - Boihaqi, Boihaqi (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2021)
Praises be to Allah who created causality events and revealed the miraculous Holy Quran in which wisdom and good tidings are rewarded. Peace and salutation be upon Prophet Muhammad SAW, the noble human being amongst all. Exegesis is an exalted field of sciences which functions to decipher Quranic verses and clarify sharia sciences related thereto, it is infact often be seen as references to any other field of sciences. Hence, the early exegesis scholars had put enormous effort in order to decipher the meaning of Quran and they bequeath tafseer to their future successors which contained compilations of hadith, the saying of His companion and tabiâ€™in. Also, the scholars had made every effort to improve human comprehension of Quran. Among all the noted exegesis scholars was Ibnu Jarir Atthabary who wrote â€œJamiâ€™al Bayan Taâ€™wil Al-Quranâ€ which used distinctive method to decipher Quran. For instance, when interpreting Quranic verses, he said, â€œthe following is the Quranic interpretationâ€¦â€, and he vowed that the tafseer are results of sanad up to a Prophetâ€™s companion or Successors, which called tafseer bilmaâ€™sur. Furthermore, when there were dispute about the meaning of Quranic Verses, he quoted various opinions, sanad, and references. Then, he would explain the most acceptable argumentation amongst all, viewed them semantically if needed, and also vowed likewise. This method, along with other Islamic theorems, was also used in deducing regulation/law (istimbath). The tafseer of Ibnu Jarir are invaluable reference for exegesis scholars. For this reason, the writer was interested in conducting discussions on â€œThe Background of Quranic Revelation Based on Atthabaryâ€™s Jamiâ€™al Bayan Taâ€™wilayat Al Quran and the Tafseerâ€™s Influences in Analyzing Most Righteous Argumentation (A study on Quranic Verses Al Ikhlash)â€. This study is a comprehensive causative study which especially discusses the contradictory argumentation in interpreting Quranic verses which has revelation background. As a matter of fact, the important findings highlighted of this research were Ibnu Jarir Atthabari is an obidient human being who mastered various branches of science related to his curriculum and was not a adhered to any specified realms. Moreover, his tafseer contains a lot of beneficial sciences for those who seek for knowledge. Finally, it is only to Allah, the writer raised his hands for help, protection, and success. Praises be to Allah for His mercy which pours all the goodness amongs us.